Jumping from relationship stability and movement (vertical, horizontal)level bottom of the foot (medial arch) and descriptive research on theplayers of Najaf to the speed events, jumping youth athletics - Sabri, Jamal; Makki, Ammar (Journal of Physical Education, 2012)
The study included five sections, as it included Title I provided and the importance of research that the elements of general fitness correct the body's safety arch of the foot, and the arc of great importance in the flexibility of movement and withstand external shocks when walking, jumping, so the multiplicity of the bones that absorbs shocks, which lies on the foot, and the research problem is to study the foot arches (media larch) whether the process of jumping from the stability or movement horizontally and vertically. The research aims to identify the relationship between fixed and mobile jump (horizontal, vertical) and the bottom of the foot arch (medial arch).Was addressed in Part II to explain some of the topics related to the research objectives, including the foot arches and its importance, and a similar study.While ensuring that Title III research methodology and procedures, where the researcher used the descriptive method survey The research community select the players team Najaf Athletics for the 2011 season the youth, who are (20) player, for the events of speed and jumping only, and the researcher to find homogeneity of both height and weight, The researcher test the main and included measuring the height of arch of the foot Anis and on the basis of this test, according to the equation Terslowere divided into two groups: (a) has the arc of normal and (b) has an arc less than normal as well as a test jump the horizontal and vertical stability and movement was processing the data statistically using Statistical Laws occasion.After the presentation and analysis of the results and discussed in Part IV of the tables, the researcher to several conclusions in Part V guarantees the several conclusions, including 1 - that the arch of the foot (medial)correlation moral and directly jumping horizontal stability and movement for the group (a), which has arc feet natural . 2 - that the arch of the foot(medial) correlation is significant jump from the horizontal stability and significant relation to jump of the horizontal movement, for the group (b), which has arc feet less than normal.There were a set of recommendations, including 1 - the need for research on all sporting events, especially those that depend on the strength of jump mainly to maintain the safety of the players they have peace of it. 2 -attention and emphasis on the use of medical shoes for the players that help keep the brackets on the normal performance during exercise.